Politics and Strategic Change Across Organizational Life Cycles - Gray, Barbara; Ariss, Sonny S. (Academy of Management Review, 1985)
This paper links research on political processes in organizations with research on organizational life cycles and strategic change. It is proposed that politics accompany strategic changes but are manifested differently at each stage of an organization's life cycle. A political life cycle model is developed in which contextual factors and strategic choices work together to evoke different political tactics during each period of the life cycle. The implications of this model for practicing managers and for research are addressed.